Prevalence of antibiotic resistance genes in drinking and environmental water sources of the Kathmandu Valley, Nepal - Amarasiri, Mohan; Takezawa, Tsubasa; Malla, Bikash; Furukawa, Takashi; Sherchand, Jeevan B.; Haramoto, Eiji; Sei, Kazunari (Frontiers in Microbiology, 2022)
Antibiotic resistant bacteria-associated infections are responsible for more than 1.2 million annual deaths worldwide. In low- and middle-income countries (LMICs), the consumption of antibiotics for human and veterinary uses is not regulated effectively. Overused and misused antibiotics can end up in aquatic environments, which may act as a conduit for antibiotic resistance dissemination. However, data on the prevalence of antibiotic resistance determinants in aquatic environments are still limited for LMICs. In this study, we evaluated the prevalence and concentration of antibiotic resistance genes in different drinking and environmental water sources collected from the Kathmandu Valley, Nepal using droplet digital PCR to understand the current situation of ARG contamination. River water and shallow dug well water were the most contaminated with ARGs. Almost all samples contained sul1 (95%), and intI1 and tet(A) were detected in 83% and 60% of the samples, respectively. Maximum ARG concentration varied between 4.2 log10 copies/100 ml for mecA and 9.3 log10 copies/100 ml for sul1. Significant positive correlations were found between ARGs (r >0.5, p < 0.01), except for mecA, qnrS, and vanA. As sul1 and intI1 were detected in almost all samples, the presence of these genes in a given sample may need to be considered as background antibiotic resistance in LMICs. Therefore, monitoring ARGs such as β-lactam antibiotic resistance genes, quinolone resistance genes, and vancomycin resistance genes may provide a better picture about the antibiotic resistance determinants in aquatic environments of LMICs.